Zinc Intakes and Health Outcomes: An Umbrella Review - Li, Jin; Cao, Dehong; Huang, Yin; Chen, Bo; Chen, Zeyu; Wang, Ruyi; Dong, Qiang; Wei, Qiang; Liu, Liangren (Frontiers in Nutrition, 2022)
It is widely accepted that the zinc element is crucial in human beings. However, some studies also pointed out that zinc intake might cause unwanted side effects and even be dangerous when overdosed. To reveal the relationship between zinc intake and health outcomes, we performed an umbrella review from the human. In total, 11 and 84 outcomes in 40 articles for dietary and supplementary zinc intake were identified. Dietary zinc intake in the highest dose would decrease the risk of overall and specific digestive tract cancers, depression and type 2 diabetes mellitus (T2DM) in adults. Supplementary zinc consumption in adults was linked to an improvement of depression, better sperm parameters, higher zinc concentration and decreased concentration of inflammatory markers. Zinc supplementation in children would reduce the incidence of diarrhea and pneumonia, improve zinc deficiency and boost growth. Dose-response analyses revealed that daily 5 mg increment of zinc was related to 14-15% lower risk of colorectal and esophageal cancer, whereas 100 mg increment was not related to prostate cancer risk.